Hematite dodecahedron crystals with high-index facets grown and grafted on one dimensional structures for efficient photoelectrochemical H2 generation. (August 2018) - Wang, Lei; Nguyen, Nhat Truong; Shen, Zhiqiang; Schmuki, Patrik; Bi, Yingpu
Abstract: Fe2 O3 polyhedrons are one of the most promising morphologies for photoelectrochemical water splitting. In spite of recent reports on the successful synthesis of various Fe2 O3 polyhedrons, the fabrication of defined photoelectrodes by anchoring the polyhedron in a suitable configuration remains a great challenge. Herein, we introduce a synthetic strategy to prepare Fe2 O3 dodecahedrons with high-index 112 facets directly anchored on a one dimensional Fe2 O3 nanoflake (110 facets) electrode. Key is that the Fe2 O3 nanoflakes act as seeds for the initiation of the growth of dodecahedral nanocrystals from an iron nitrate solution. The initial single crystals consist of Fe3 O4 with exposed 110 basal surfaces that then in a thermal step can be converted to hematite with 112 facets. The resulting single crystal (bi-crystal) hematite photoanode demonstrates a high efficiency for solar water splitting with an excellent photoresponse due to the synergistic effects of direct grafting of the light harvesting and reactive polyhedron and the 1D transport geometry. Under optimized conditions the hematite polyhedrons on nanoflake-structure show photocurrent densities of 2.4 mA cm −2 at 1.23 VRHE and 3.5 mA cm −2 at 1.5 VRHE under AM 1.5 G simulated sunlight. Graphical abstract: A simple and facile strategy is used to propare Fe2 O3 dodecahedrons with high-index 112 facets directly anchored on a one dimensional Fe2 O3 nanoflakes structure. The resulting single crystal (bi-crystal) hematite photoanode demonstrates a high efficiency for solar water splitting with an excellent photoresponse due to the direct grafting of the light harvesting and reactive dodecahedrons to the transport geometry. fx1 Highlights: First report of Fe2 O3 dodecahedrons with high-index 112 facets on 1D structures. Fe2 O3 nanoflakes as seeds for the growth of dodecahedral nanocrystals. A high photocurrent of 2.4 mA cm-2 at 1.23 VRHE is obtained for polyhedrons. Synergistic effects of light harvesting and 1D transport geometry. A stable electrode configuration is established for solar water splitting systems.